Identifikasi Faktor-Faktor Yang Mempengaruhi Nilai Idle Time (IT) Di Pelabuhan Dumai (Dermaga A) - Feri Setiawan; Trimaijon Trimaijon; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Ports are place for docking, shipping and unloading. Any activities have done by any ships have some difference. Problem due shipping activities is idle time (IT) during working caused by several factors raining, loading, regulation, damaged crane ships, etc. Other problem from shipping a factor classification is necessity.Factors that cause idle time are classified into three groups. 1) Human error including waiting for truck, operator, worker, and delay for work. 2) Technical errors including emptying storage, damaged equipment, and damaged ship, 3) Factor fromnature including rain and tides. All these factors cause delays in shipping. Based on the analysis, the most dominant factor in fluctuation is due damaged equipments with the total number of hours were 283.6 hours a year. Mean for the dominant factor due damaged equipments waste 23.64 hours per month. Solution of the problems that occur are the good planning on shipping and co-ordination between companies and port management.Keywords: harbor, Idle time, loading and unloading, equipment failure